Molecular identification and biocontrol of ochratoxigenic fungi and ochratoxin A in animal feed marketed in the state of Qatar. Issue 1 (January 2023) - Alsalabi, Fatma Ali; Hassan, Zahoor Ul; Al-Thani, Roda F.; Jaoua, Samir
Abstract: Ochratoxin A (OTA) is a toxic fungal metabolite produced by some Aspergillus and Penicillium species. This work was designed to explore the presence of OTA and ochratoxigenic fungi in feed grains marketed in Qatar and their biological control by a bacterium ( Burkholderia cepacia ). Significantly higher levels of OTA were detected in mixed grains samples (144.59 ± 6.63 μg/kg), compared to the maize (25.27 ± 1.89 μg/kg) and wheat (3.37 ± 0.11 μg/kg). OTA-producing fungi ( A. niger, A. ochraceus, A. westerdijkiae, A. carbonarius and P. verrucosum ) were identified on the basis of their morphological features as well as through polymerase chain reaction (PCR). Putative ochratoxigenic polyketide genes in these isolates were evidenced by using primers AoOTA-L/AoOTA-R (in A. ochraceus and A. westerdijkiae ), AoPks1/AoPks2 (in A. niger and A. ochraceus ) and PenPks1/Penpks2 (in P. verrucosum ). On synthetic media, A. westerdijkiae showed the highest OTA synthesis (5913 ± 576 μg/kg) than the closely related A. ochraceus (3520 ± 303 μg/kg), A. carbonarius (3064 ± 289 μg/kg) and P. verrucosum (3030 ± 710 μg/kg). Burkholderia cepacia cells and culture extract showed promising biological control potentials against OTA producing fungi. On the basis of these findings, it can be concluded that animal feed samples are generally contaminated with OTA-producing fungi as well as OTA, and Burkholderia cepacia CS5 exhibits promising antifungal activities. Graphical abstract: Image 1